PENGARUH BEBAN KERJA, KEPUASAN KERJA, SELF EFFICACY DAN TIME BUDGET PRESSURE PADA KINERJA AUDITOR - Suprapta, Kadek Ricky Ardie; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
This study aimed to examine the effect of workload, job satisfaction, self-efficacy and time budget pressure on the performance of auditors public accounting firm in the province of Bali. The theory used in this research is the Expectacy Theory. The study population was all auditors working in the public accounting firm in Bali as many as 82 people in 2016. The number of samples used in this study were 81 respondents to the sampling technique purposive sampling method. The data collection was conducted by questionnaire. Data analysis technique used is multiple linear regression analysis. The results showed that Workload and time budget pressure have negative effect on the performance of auditors in KAP Bali Province. Job satisfaction and self efficacy positive effect on the performance of auditors in KAP Bali Province.
Keywords: workload; job satisfaction; self-efficacy; time budget pressure